1985
DOI: 10.1037/0278-6133.4.6.579
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral sequellae associated with adrenergic-inhibiting antihypertensive agents: A critical review.

Abstract: Adrenergic-inhibiting antihypertensive drugs, most notably the beta-blockers and alpha-agonists, have been shown to influence a variety of central nervous system (CNS) functions. In some instances the use of these drugs has also been reported to lead to serious psychiatric complications. Despite the clinical significance of these effects and the potential threat to treatment adherence the underlying mechanisms are poorly understood. This article critically evaluates the existing research in six major areas: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…2,15,16 According to the results of our study educational, social as well as psychological factors might play the dominant role in the development of impotence as has been indicated in other studies dealing with quality of life in patients with coronary heart disease. 1,17 Further work is however needed to clarify the role of betablockers on the erectile function in different and larger populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,15,16 According to the results of our study educational, social as well as psychological factors might play the dominant role in the development of impotence as has been indicated in other studies dealing with quality of life in patients with coronary heart disease. 1,17 Further work is however needed to clarify the role of betablockers on the erectile function in different and larger populations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Apart from side effects predominantly affecting cardiac and lung function most patients are afraid of negative interference with their sex life while taking beta-blockers. 1 In the present prospective, randomized and placebo-controlled study patients in their fifties suffering from atherosclerotic heart disease were asked to evaluate their sexual performance before and after treatment with low dose beta-blockers or placebo. According to an anonymous standardized questionnaire questions dealing with various aspects of erectile dysfunction had to be answered at the beginning and at the end of the Beta-blockers and impotence D Franzen et al study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported inconsistent findings, with some betablockers producing an increase in performance and others a decrease (reviewed in Rosen and Kostis 1985). It has been suggested that drugs with greater intrinsic sympathomimetic activity, e.g.…”
Section: Saccadic Eye Movement Parametersmentioning
confidence: 97%
“…Yet, it is well known that the cope with mental challenges and stressors compounds may cause mild subjective symptoms (Brodsky et al, 1987;Gengo et al, 1988) have (Rosen & Kostis, 1985) such as tiredness, fatigue been reported. and sleep disturbances, which are considered to Although the positive effects of 3-adrenobe CNS-related (Drayer, 1987;Frohlich et al, ceptor blockers are presumed to be related to 1983) as well as changes in mood (Avorn et al, their P-adrenoceptor blocking properties, the 1986; Currie et al, 1988).…”
Section: Introductionmentioning
confidence: 99%